Luteinizing hormone changes in gonadotropin-releasing hormone antagonist protocol in in vitro fertilization cycles: A cross-sectional study - Batool Hosein Rashidi; Roya Kabodmehri; Mamak Shariat; Ensieh Shahrokh Tehraninejad; Alireza Abdollahi; Maryam Bagheri; Fedieh Hagholahi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Because of the unexpected and often dramatic inhibition of luteinizing hormone (LH) secretion related with the usage of gonadotropin-releasing hormone (GnRH)-antagonist, there has been a probable need for exogenous LH supplementation. There is a basic and clinical evidences that show late development of follicle needs an LH but there is a threshold for LH requirements during folliculogenesis. Objective The purpose of this study was to evaluate the changes in serum LH and the identification of patients who benefit from the addition of LH. Materials and Methods Seventy volunteers for antagonist protocol in IVF cycle were enrolled in this prospective cross-sectional study. The study was carried out in Reproductive Health Research Center, University of Medical Sciences between July 2016 and February 2016. Serum LH level was estimated 24 h before and after the first (GnRH) antagonist injection. The primary outcome was the serum level of LH and its change in the three groups and the secondary outcome was Egg and Embryo quality. Results LH changes above or below 50% had no effect on the number of follicle, the number of oocyte, Germinal vesicle oocyte, metaphase 1 oocyte, metaphase 2 oocyte, endometrial thickness, and chemical and clinical pregnancy. Conclusion We evaluated the changes of serum LH in the patients who were entered in the antagonist protocol. Our study showed no significant difference in LH levels 24 h before and after the injection of the antagonist between the three groups, and LH changes did not affect the outcome of pregnancy.